La cuarentena externa de artiodáctilos de vida salvaje desde Namibia a Cuba - Bolaños, R. (2015)
In Cuba for several years not imported wild animals from the African continent and this important donation was received from Namibia called Noah?s Ark II, considered the largest held in the country?s history. The present study shows the results of external quarantine of the 8 species of artiodactyls introduced in the country and with final destination at the National Zoo Park. Artiodactyls species were identified as African Buffalo (Syncerus caffer), Cape Eland (Taurotragus oryx), Roan Antelope (Hippotragus equinus), Greater Kudu (Tragelaphus strepsiceros), Hartebeest (Alcelaphus lichtensteinii), Gemsbok or Oryx (Oryx gazella), Impala (Aepyceros melampus) and Springbok (Antidorcas marsupiales). One hundred nine animals were investigated against 20 diseases. The laboratory results showed that 74.3% of all animals in quarantine were negative for 15 of the 20 diseases, 4% trypanosomiasis suspects and 22% positive for bluetongue, theileriosis, anaplasmosis and epizootic hemorrhagic disease. Sex relating these results showed that the highest percentage of negative animals appeared in populations with 77% females, while in males was lower with 69%. Arrived in the country a total of 59 adults and 5 calf Springbok meeting with the evaluate aspects and points made in the import protocol, so as apparently healthy animals and serologically negative to diseases of interest